Build it and they will come: Outcomes from a successful cardiac rehabilitation program at an Aboriginal Medical Service - Dimer, Lyn; Dowling, Ted; Jones, Jane; Cheetham, Craig; Thomas, Tyra; Smith, Julie; McManus, Alexandra; Maiorana, Andrew (CSIRO Publishing, 2013)
Objective. Cardiovascular disease (CVD) is the leading disease burden in Aboriginal Australians, but culturally appropriate cardiac rehabilitation programs are lacking. We evaluated the uptake and effects on lifestyle, and cardiovascular risk factors, of cardiac rehabilitation at an Aboriginal Medical Service (AMS). Methods. The program involved weekly exercise and education sessions (through ‘yarning’) for Aboriginal people with or at risk of CVD. Participants’ perceptions of the program and the impact on risk factors were evaluated following 8 weeks of attendance. Results. In twenty-eight participants (20 females) who completed 8 weeks of sessions, body mass index (34.0 ± 5.1 v. 33.3 ± 5.2 kg m–2; P < 0.05), waist girth (113 ± 14 v. 109 ± 13 cm; P < 0.01) and blood pressure (135/78 ± 20/12 v. 120/72 ± 16/5 mmHg; P < 0.05) decreased and 6- min walk distance increased (296 ± 115 v. 345 ± 135 m; P < 0.01). ‘Yarning’ helped identify and address a range of chronic health issues including medication compliance, risk factor review and chest pain management. Conclusions. AMS-based cardiac rehabilitation was well attended, and improved cardiovascular risk factors and health management. An AMS is an ideal location for managing cardiovascular health and provides a setting conducive to addressing a broad range of chronic conditions.